2023
DOI: 10.1002/adma.202207966
|View full text |Cite
|
Sign up to set email alerts
|

Van der Waals‐Interface‐Dominated All‐2D Electronics

Abstract: The interface is the device. As the feature size rapidly shrinks, silicon‐based electronic devices are facing multiple challenges of material performance decrease and interface quality degradation. Ultrathin 2D materials are considered as potential candidates in future electronics by their atomically flat surfaces and excellent immunity to short‐channel effects. Moreover, due to naturally terminated surfaces and weak van der Waals (vdW) interactions between layers, 2D materials can be freely stacked without th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 252 publications
(214 reference statements)
0
13
0
Order By: Relevance
“…[164] Due to their extremely thin thickness, 2D vertical heterostructures provide a short diffusion distance for charge carriers. [165,166] In contrast to laterally stacked heterojunctions, vertically stacked heterostructures offer a larger surface area for the interface of layered materials and involve tunneling effect between the two layers, making it highly suitable for photosensitive device applications. [167] Vertical van der Waals heterostructures combined with ambipolar 2D semiconductors allow for the integration of highly disparate materials with crystal lattice mismatching.…”
Section: Discussionmentioning
confidence: 99%
“…[164] Due to their extremely thin thickness, 2D vertical heterostructures provide a short diffusion distance for charge carriers. [165,166] In contrast to laterally stacked heterojunctions, vertically stacked heterostructures offer a larger surface area for the interface of layered materials and involve tunneling effect between the two layers, making it highly suitable for photosensitive device applications. [167] Vertical van der Waals heterostructures combined with ambipolar 2D semiconductors allow for the integration of highly disparate materials with crystal lattice mismatching.…”
Section: Discussionmentioning
confidence: 99%
“…Given the needs of IoT application and low power dissipation, self-powered photodetectors that convert light into electric signals in the absence of external bias have ushered in research and development boom in a variety of fields like thermal imaging, surveillance, optical communication, environmental monitoring, and so forth. Especially, 2D vdW heterostructures driven by the built-in electric field provide a degree of freedom for self-powered photodetection with on-chip integration technology, which benefit from adjustable atomic thicknesses, negligible lattice mismatching constraints, the strong layer-by-layer coupling effect, etc. A wealth of all-2D vdW SHJ devices fabricated by the artificial stacking or vdW epitaxy techniques have been reported to realize self-powered photodetection. For example, Xin et al reported an artificial stacked GeSe/MoS 2 vdW heterojunction photodetector with a moderate EQE of 24.2% .…”
Section: Introductionmentioning
confidence: 99%
“…Graphene (Gr) is a 2D semimetallic material composed of a single layer of carbon atoms. Although it is known to have a zero bandgap, in which the conduction and valence bands cross at the Dirac point, it can effectively suppress MIGS owing to the VdW contact. Furthermore, when Gr is in contact with the metal, a charge-sharing effect occurs from Gr to the metal, which aligns the FLs on both sides of the contact. Considering these features, Gr is a qualified interlayer candidate for a universal MIS contact structure suitable for both n- and p-type semiconductors.…”
Section: Introductionmentioning
confidence: 99%